Courting celebrity : the autobiographies of Angela Veronese and Teresa Bandettini - Ward, Adrienne, 1957-; Ward, Adrienne, 1957-; Zanini-Cordi, Irene; Zanini-Cordi, Irene; Veronese, Angela, 1778-1847; Veronese, Angela, 1778-1847; Bandettini, Teresa, 1763-1837; Bandettini, Teresa, 1763-1837 (Toronto Italian studies., 2023)
"In 1826 Angela Veronese, a gardener's daughter, wrote and published the first modern autobiography by an Italian woman. Veronese's account focuses on her unique experience as a peasant girl who came of age among the Venetian elite, and details how she attained a certain renown in and out of Italy by improvising, writing, and publishing her own lyrics. Courting Celebrity is a bilingual annotated edition of Veronese's autobiography. To better elucidate Veronese's thinking, the book includes the autobiographical writing of another contemporary Italian poet, Teresa Bandettini, a well-known Tuscan poet-improviser. The book offers a substantial sample of Veronese's poems, translated and in the original. These compositions, together with detailed bibliographical documentation, point to the success of Veronese's autobiographical enterprise and offer an unparalleled view of both high society and popular culture at the time. In doing so, this text illustrates women's practice in two key literary genres, poetry and autobiography, and illuminates the strategies of women's self-fashioning and pursuit of celebrity."--